Averroe’s laugh : The funny problem in Averroist gnoseology - Karmy, Rodrigo (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This essay argues that the averroist gnoseology developed in the Great Commentary on Aristotle´s De Anima by the cordovan philosopher (Averroes) has a comic nature. In this sense, this gnoseology can work against the grain of the tragedy and the way in which it, as has been worked by Phillipe Lacoue-Labarthe, turns human being into a subject, giving him a “being of his own”. The doctrine of the separate, unique and eternal Intellect, far from constituing a conception opposed to tragedy,would become its interruption: a moment of suspensión of the becoming subject of man that is not resolved in the configuration of the subject and the attribution of his “proper being” but in the gesture that exposes the mask as a relationship of use, rather tan the substancialization of the person and property. In this light the averroist gnoseology would be “comic” rather tan “tragic” since it interrupts the operation of appropiation.
Keywords: averroism; intellect; tragedy; comedy